A NOVEL IDEA FOR QR BASED SMART ADMIT CARDS - N.Kanya; S.Kowcigan; Dahlia Sam; C.Tamil Selvi; S.Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Admit card also sometimes referred to as a Hall Ticket, is an essential document for students to enter the examination hall. Every candidate is provided with a card containing a unique barcode instead of paper printed hall tickets. It will display the exam hall plan of an individual and the information in the QR code along with row and column number which defines the seating arrangement of an individual. Candidates just have to scan their cards during the examination time. The conventional method for recording understudy participation is that an educator calls understudy names individually what’s more, records their nonappearance or nearness status. It generally expends much of the time and some of the time causes blunders. Accordingly, a few educators may decide not to record understudy participation, and this could influence scholastic learning and result. Albeit numerous Self Identification strategies have been investigated, the whole preparing time is like the customary one. A framework that brings down understudies participation utilizing QR code. Each understudy is furnished with a card containing an extraordinary QR code. Understudies simply need to examine their cards before webcam and the framework notes down their participation according to dates. Each QR code contains an extraordinary id for understudies. Framework at that point stores all the understudies’ participation records and creates a defaulter list. It additionally creates a general report to exceed expectations sheet for the administrator. Such kind of use is exceptionally helpful in school just as in school for day by day participation.